Ecotourism Development Strategy of Pelawan Forest in Central Bangka, Bangka Belitung - Henri Henri; Luchman Hakim; Jati Batoro (Journal of Indonesian Tourism and Development Studies, 2017)
Ecotourism has a very important role in increasing the community income, cultural preservation, and environmental conservation efforts at a tourist attraction. This study aims to create the ecotourism development strategy in Pelawan Forest by involving local communities. Data collection techniques in this study using distributing questionnaires to tourists. Data were analyzed using a Likert scale analysis, IFAS/EFAS analysis, SWOT analysis to formulate ecotourism development strategy viewed factors internal and external as well Grand strategy matrix. The results research using Likert scale showed that the various attractions i.e. the area that is still awake, unique flora and fauna, the existence of alternative tourism can become a tourist attraction potential. Meanwhile, the potential demand for tourism is mostly students and employees. Ecotourism development of Pelawan Forest based on SWOT analysis can be offered by involving local communities and stakeholders in support of sustainable tourism. The position of the Grand Strategy Matrix lies in the ordinate quadrant 2, is characterized by a weak competitive position in fast growing market. Therefore, it is necessary to take counteractive action so that the ability to compete effectively is stronger and can find its space in a more competitive environment, thus becoming a sustainable ecotourism.Keywords: Â Development strategy, ecotourism, Pelawan Forest.